ANALYSIS OF BED USE EFFICIENCY WITH BARBER JOHNSON GRAPH AS AN EFFORT TO REDUCE THE WAITING TIME OF INPATIENTS IN THE EMERGENCY ROOM - Duana, Farma; Amarin Yudhana; Ardi Bastian (Journal of Hospital Management and Services, 2025)
This study analyzed the efficiency of bed use using the Barber Johnson graph as an effort to reduce the length of waiting time for inpatients in the emergency room of Wava Husada Kepanjen Hospital. The research method used a mixed design with quantitative data collection to measure efficiency indicators such as BOR, LOS, TOI, and BTO, as well as qualitative interviews to explore the factors that cause long waits. The results showed high bed occupancy rates and bed turnover, which contributed to the length of patient wait times. This study suggests optimizing bed management and improving organizational processes to accelerate patient services. These findings provide practical implications for hospital management to improve patient flow and emergency service efficiency.